1979
DOI: 10.1007/bf01414779
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic quadrupole and hexadecapole moments of rare earth nuclei

Abstract: The theoretical calculations of multipole moments of even-even rare earth nuclei are presented. The potential energy surface is evaluated by the shell correction method. The condition ensuring the equality of the density distribution of the macroscopic liquid droplet part of the potential energy and the density generated by the single particle potential is added. A single particle Nilsson potential is used. New, less stiff potential surfaces versus e~ are obtained while the multipole moments calculated at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…It was therefore argued (see Refs. [138,139] and references quoted therein) that a mapping between the two sets of shape deformations can be best achieved by using the surface multipole moments defined asQ λ ≡ r 2 Y λ0 , which have a much softer radial dependence than volume moments. Deformation parametersβ l can therefore be extracted by requiring that the set of equations for dimensionless surface moments [138,139] Q λ (β l )…”
Section: B Determination Of Microscopic Ldm Deformationsmentioning
confidence: 99%
“…It was therefore argued (see Refs. [138,139] and references quoted therein) that a mapping between the two sets of shape deformations can be best achieved by using the surface multipole moments defined asQ λ ≡ r 2 Y λ0 , which have a much softer radial dependence than volume moments. Deformation parametersβ l can therefore be extracted by requiring that the set of equations for dimensionless surface moments [138,139] Q λ (β l )…”
Section: B Determination Of Microscopic Ldm Deformationsmentioning
confidence: 99%
“…The values of the parameters of the single particle potential depend sensitively on the assumed equilibrium deformation. In the papers [2][3][4] it was found that the shape of the microscopic density distribution of the nucleus does not agree with the shape of the equipotential surface of the single particle potential which generates the density distribution. This means that one gets two different sets of equilibrium deformation parameters.…”
mentioning
confidence: 96%
“…Because of the large difference in equilibrium deformations of the potential (~) and the density (e~) obtained with the simple consistency condition of Ref. 4 it seems to us that it was necessary to find a new set of (x, #) values for correctness (2). To do this we followed the method we have used previously in [5].…”
mentioning
confidence: 98%
See 2 more Smart Citations